Incorporation of side chain flexibility into protein binding pockets using MTflex. Issue 20 (15th October 2016) - Bansal, Nupur; Zheng, Zheng; Merz, Kenneth M.
Graphical abstract: Abstract: The plasticity of active sites plays a significant role in drug recognition and binding, but the accurate incorporation of 'receptor flexibility' remains a significant computational challenge. Many approaches have been put forward to address receptor flexibility in docking studies by generating relevant ensembles on the energy surface. Herein, we describe the Movable Type with flexibility (MTflex ) method that generates ensembles on the more relevant free energy surface in a computationally tractable manner. This novel approach enumerates conformational states based on side chain flexibility and then estimates their relative free energies using the MT methodology. The resultant conformational states can then be used in subsequent docking and scoring exercises. In particular, we demonstrate that using the MTflex ensembles improves MT's ability to predict binding free energies over docking only to the crystal structure.